Advanced structural mechanics an introduction to continuum mechanics and structural mechanics - Johnson, David, 1942 August 2- (Thomas Telford, 2000)
This text is adressed to professional engineers, offering a broad introduction to the principal themes of continuum mechanics and structural dynamics. This edition includes a greater focus on worked examples, problems and solutions to engage the reader.